Georgia Architectural and Historic Properties Survey of Quitman [298] Highway 221, south of Quitman (just out of city limits), Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Quitman [298] Highway 221, south of Quitman (just out of city limits), Valdosta, Ga. December 1980. Two story house of irregular plan. Hipped, gabled roof. Surrounding shed porch with turned spindle posts. Clapboard siding. Sash windows with 2/2 lights. Shutters. Transom over door. Interior chimney. Set on brick piers. Second story central balcony. Set in a grove of oak trees. Good condition. Date of Construction: c. 1890. Very nice example of a turn of the century country house.
Two story house of irregular plan. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 767 KB (786,249 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.); Brooks County (Ga.)